Mental accounting: Global research trends and Indonesia's research position - Muthohhari, Abdullah Hanif; Kurniawanti, Ika Atma; Utama, Anak Agung Gde Satia; Edward, Oswald Timothy (Journal of Multiperspectives on Accounting Literature, 2026)
Purpose: As mental accounting (MA) influences critical economics and finance phenomenon, understanding research trends and Indonesia's research position can contribute to the development of accounting policies aligned with the local context. This study offers a bibliometric analysis of pertinent papers in mental behavioral accounting. Methodology/approach: By analyzing 271 articles from the Scopus database published from 2015 to 2024, this study uses bibliometric analysis to identify global research trends and Indonesia’s position in MA. Findings: The analysis indicates that the prior research in MA over decade will focus on prospect theory, consumer behavior, investment decision-making, behavioral biases, and financial literacy. Our data indicates that mental accounting researchers globally must reapply mental accounting principles across diverse domains. Practical implications: This study recommends that researchers expand their analyses by integrating MA with the Indonesian economic framework and concentrate to the advancement of MA research globally. Originality/value: This study also provides additional analysis regarding the progress of MA research in Indonesia by finding its research position.